Self-Perception and the Relation to Actual Driving Abilities for Individuals With Visual Field Loss - Andersson, Jan; Bro, Tomas; Lajunen, Timo (Frontiers in Human Neuroscience, 2022)
Background: The literature clearly indicates that individuals with VFL are unsafe drivers on a group level. However, many drivers with VFL can be safe on an individual level. The literature also suggests that self-perception, beliefs, and insights of one’s own capabilities are related to driving performance. This study had three aims: (1) to investigate self-perceived driving capability ratings for individuals with VFL; (2) to compare these ratings between groups with different medical conditions associated with VFL (stroke, glaucoma, and diabetes); and (3) to relate the self-perception ratings to actual driving performance in an advanced driving simulator. Method: Participants comprised 723 individuals whose driver’s license had been withdrawn because of VFL and 92 normally sighted elderly individuals. All participants completed a background survey, rated difficulties with different traffic situations, rated their strengths and weaknesses as drivers, and rated aspects that were important for causing traffic accidents. Of the VFL group participants, 264 also completed a simulator-based driving test that they knew could lead to renewal of their driving license. VFL participants and normally sighted was at the same age when they completed the simulator driving test. Results: Overall, individuals with VFL rated their capabilities as high on all instruments and scales used, even higher than the elderly normally sighted control group. The only VFL etiology group that rated lower than other groups was the diabetes group. Safety orientation and internal control orientation values were best at discriminating between VFL participants in terms of self-perception of driving performance. Participants categorized as “high” in terms of safety skills and internal control were more modest in their ratings. Finally, participants who passed the simulated driving test did not differ from those who failed, in any of the self-perception measures. Conclusion: Self-perception ratings among individuals with VFL were higher than those of normally sighted elderly individuals. Self-assessed skills did not predict driving performance. Groups with different VFL etiologies rated similarly. Self-ratings of driving abilities cannot be used to assess actual driving performance. Actual driving tests (on road or in the simulator) are necessary to discriminate between safe and unsafe drivers with VFL.